Pengaruh Manajemen Sumber Daya Manusia Melalui Kecerdasan Spiritual Terhadap Kinerja Karyawan Di PT. Catur Adiluhur Sentosa Palembang - Dwi Aldino (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This study aims to determine the effect of human resource management through spiritual intelligence on employee performance at PT. Caturadiluhur Sentosa Palembang, Human resource management and spiritual intelligence are factors that are needed to improve employee performance, with a high quantity and quality of employee work, it can increase the enthusiasm and performance of other employees. The research method in this research is quantitative, the research data analysis technique used is path analysis or path analysis. Data processing is assisted by the SPSS for windows version 26.00. research data collection techniques through distributing questionnaires with sampling techniques using random sampling totaling 101 respondents. The results of the study show that human resource management influences spiritual intelligence, human resource management influences employee performance, spiritual intelligence influences employee performance, human resource management and spiritual intelligence influences employee performance, and human resource management influences employee performance with spiritual intelligence as an intervening variable.